Avaliação do potencial da arrecadação do ICMS no Estado do Piauí - Breuel, Sérgio Roberto Genuíno de Oliveira (2010)
The aim of this study is to evaluate and analyze the technical efficiency of collection of the Tax on Circulation of Goods and Services (ICMS) of the state of Piauí. It seeks to investigate whether the constitutional transfers from the federal government, controlling for other determinants, makes the machine less efficient tax collecting function of these resources. The approach used to achieve these goals was the econometric model of stochastic production function model that allows the technical inefficiency in collection. The estimated results of this model suggest that the ICMS tax collecting machine was technically efficient in the period. In this sense, the constitutional funds for the state showed no impact on the collection of ICMS. Moreover, the macroeconomic policies of the federal government seem to have positively influenced the collection of this tax.